Use of a fiber optic distributed temperature sensing system for thermal response testing of ground-coupled heat exchangers. (January 2018) - Herrera, Christian; Nellis, Gregory; Reindl, Douglas; Klein, Sanford; Tinjum, James M.; McDaniel, Adam
Highlights: A fiber optic distributed temperature sensing system is used within a ground-coupled heat exchanger during a thermal response test. The highly resolved temperature data set provides the ability to discern stratification of ground properties that occur along the depth of a bore. These results allow the determination of spatially resolved ground properties as opposed to a single, effective set of ground properties. Abstract: A thermal response test (TRT) is commonly conducted at a site proposed for the installation of a ground-coupled heat pump system. The purpose of the TRT is to gather local data to infer thermal properties of the soil. Accurately estimating soil thermal properties enables designers to size the geofield appropriately and supports improved simulations of ground heat exchanger (GHX) systems to better estimate the system performance over both shorter-term and longer-term intervals. This paper reports on the use of a fiber optic distributed temperature sensing system to spatially resolve the temperatures along the entire length of a U-tube within a vertical bore geothermal well. The fiber optic probe inside the U-tube provides spatial temperature data at a 2-m resolution throughout the duration of a TRT. The spatial temperature data within the U-tubes provided by a fiber optic probe offers the potential to determine other characteristics of a test bore, such as ground properties as a function of depth, which will enable much more accurate ground heat exchanger models in the future. An added outcome of this technique is a direct means to observe stratification of fluid temperatures which is another indicator of differences in ground properties that may occur along the depth of a vertical bore.